An Objective Estimation of Air-Bone-Gap in Cochlear Implant Recipients with Residual Hearing Using Electrocochleography - Koka, Kanthaiah; Saoji, Aniket A.; Attias, Joseph; Litvak, Leonid M. (Frontiers in Neuroscience, 2017)
Although cochlear implants (CI) traditionally have been used to treat individuals with bilateral profound sensorineural hearing loss, a recent trend is to implant individuals with residual low-frequency hearing. Notably, many of these individuals demonstrate an air-bone gap (ABG) in low-frequency, pure-tone thresholds following implantation. An ABG is the difference between audiometric thresholds measured using air conduction (AC) and bone conduction (BC) stimulation. Although behavioralbehavioral AC thresholds are straightforward to assess, BC thresholds can be difficult to measure in individuals with severe-to-profound hearing loss because of vibrotactile responses to high-level, low-frequency stimulation and the potential contribution of hearing in the contralateral ear. Because of these technical barriers to measuring behavioral BC thresholds in implanted patients with residual hearing, it would be helpful to have an objective method for determining ABG. This study evaluated an innovative technique for measuring electrocochleographic (ECoG) responsesusing the cochlear microphonic (CM) response to assess AC and BC thresholds in implanted patients with residual hearing. Results showed high correlations between CM thresholds and behavioral audiograms for AC and BC conditions, thereby demonstrating the feasibility of using ECoG as an objective tool for quantifying ABG in CI recipients.